Relating foveal and parafoveal processing efficiency with word-level parameters in text reading - Heikkilä, Timo T. (Elsevier, 2025)
The study examined whether word-level eye-movement patterns in text reading can be predicted by individual differences in foveal and parafoveal word processing efficiency. Individual differences in lexical skills were gauged by presenting words and pseudowords with short exposure times in the fovea (30–60 ms) and at varying eccentricities in the parafovea. Lexical decision was used to index orthographic processing, word naming to index phonological processing and pseudoword naming to index grapheme-phoneme decoding. The Random Forests statistical technique was used to assess the relative importance of individual difference measures in predicting readers’ eye-movement patterns. The results show that individual differences in foveal word processing efficiency are better predictors of both foveal and parafoveal word processing during reading than differences in parafoveal processing efficiency. Results indicate that individual variability in foveal word recognition skills are better determinants of reading fluency among adult readers than variability in parafoveal word recognition skills.